1956
DOI: 10.1039/jr9560002010
|View full text |Cite
|
Sign up to set email alerts
|

394. Condensation products of phenols and ketones. Part X. The structure of dianin's compounds, a unique inclusion-forming substance

Abstract: A product, " Dianin's compound,'' first prepared in 1914 from phenol and mesityl oxide, is shown to be 4-P-hydroxyphenyl-2 : 2 : 4-trimethylchroman (111). Oxidation yields 2 : 2 : 4-trimethylchroman-4-carboxylic acid, and thermal degradation gives phencl and 2 : 2 : 4-trimethylchromen. The latter compound has been synthesised and yields Dianin's compound by addition of phenol.Dianin's compound forms inclusion compounds with over fifty widely differing organic solvents, some inorganic gases, and with iodine. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 0 publications
1
57
0
Order By: Relevance
“…This was converted to the unsolvated form of 1 by bubbling COz gas through a basic solution of the ethanol adduct in H20 (2). The resultant white powder was dissolved in carbon tetrachloride to produce the CCl4 adduct of l (2). Single crystals were obtained by slow evaporation; samples for the X-ray powder diffraction were obtained by rapid recrystallization.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was converted to the unsolvated form of 1 by bubbling COz gas through a basic solution of the ethanol adduct in H20 (2). The resultant white powder was dissolved in carbon tetrachloride to produce the CCl4 adduct of l (2). Single crystals were obtained by slow evaporation; samples for the X-ray powder diffraction were obtained by rapid recrystallization.…”
Section: Methodsmentioning
confidence: 99%
“…Dianin's compound (1) was prepared from phenol and mesityl oxide according to the method of Baker et al (2), and isolated as the ethanol adduct. This was converted to the unsolvated form of 1 by bubbling COz gas through a basic solution of the ethanol adduct in H20 (2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All ketones were purified by column chromatography and (or) vacuum distillation prior to use. Dianin's compound (1) was prepared and purified by the method of Baker et al (33). Unsolvated Dianin's compound was obtained by sublimation of the ethanol complex at 140°C and 1 Torr (mp 166 -167°C).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent work has shown that Dianin's compound is capable of including a wide variety of organic molecules, including ketones (33). X-ray crystallography (34,35) reveals that six molecules of compound 1 form a cage and that theSages are hourglass shaped with a length of approximately 11 A, a mid-pointowidth of 4.2 A, and a maximum upper and loyer width of 6.3 A.…”
Section: Introductionmentioning
confidence: 99%